Deploying a rapid point-of-care polymerase chain reaction test for SARS-CoV-2 in a clinical research unit to ensure healthy volunteer safety - Brouwer, J.L (Future Medicine Ltd., 2021)
The entire world was severely affected by the outbreak of the SARS-CoV-2 virus. Early phase clinical research was no exception and clinical healthy volunteer trials were halted across the globe. To enable continuation of development of new drugs, we developed a testing strategy for nonsymptomatic trial participants in an early stage of the outbreak. A point-of-care polymerase chain reaction test combined with a gold standard polymerase chain reaction test and strict social distancing and hygiene measures limited the number of infected subjects entering our clinical research units and reduced further spread for the duration of the clinical trial. Thus, proving efficacy of this strategy to allow safe and effective continuation of early phase clinical trials during the COVID-19 pandemic. © 2021 Newlands Press.